To own your name in gold - Palacios, Ainhoa, author; Altschul, Andrew, advisor; McConigley, Nina, committee member; Quijada, Martin, committee member (Colorado State University. Libraries, 2025)
To Own Your Name in Gold is a collection of interconnected stories exploring the intricate relationship between identity, migration, and the pursuit of the American Dream. Through the lens of a mother and daughter navigating their new lives in the United States, this collection examines the emotional and cultural costs of assimilation. The stories trace their evolving relationship as they balance nostalgia for the home they left behind with the pressures of adapting to an unfamiliar world. By centering the experiences of first- and second-generation immigrants, the collection interrogates both the promises and illusions of the American Dream—what it offers and what it demands in return. At its core, this work considers the weight of names, language, and heritage in the process of self-definition. The stories highlight the tensions between survival and belonging, between remembering and reinventing, and between the narratives imposed upon immigrants and the stories they craft for themselves. To Own Your Name in Gold ultimately seeks to illuminate the fractures and resilience found in the immigrant experience, portraying not just what is gained, but also what is lost in the journey toward belonging.